Malignant melanoma in the Czech Republic: incidence and mortality according to sex, age and disease stage - Vranova, Jana; Arenbergerova, Monika; Arenberger, Petr; Vrana, Antonin; Zivcak, Jozef; Kolarova, Hana; Rosina, Jozef (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2014)
BACKGROUND: The Czech Republic has reported one of the highest incidence rates of cutaneous melanoma (CM) in Europe and the rate continues to rise. Our study undertook a detailed investigation of the incidence and mortality of melanoma relative to sex, age and disease stage. The main goals were to elucidate the causes of the rising trends and explain the differences in development relative to sex, age and disease stage. METHODS AND RESULTS: The estimated annual percentage change (EAPC) using the Joinpoint Regression Model was calculated separately for men and women for all age categories and for all T stages of TNM classification. The EAPC for women was slightly higher than for men. This was only found in melanomas thinner than 1 mm (T1). For all other stages (T2, T3 and T4) the situation was worse in men. A higher incidence rate of CM and the higher value of EAPC were found for women in younger age categories (up to 49 years). In the next age category, from 50 to 59 years, the incidence of CM was comparable in both sexes as well as the EAPC. In the older age categories, i.e. 60 years and older, a significant increase was found predominantly in men. The mortality rates were only comparable between men and women in the 20 to 29 year age group. In all other categories there was a higher mortality for men. CONCLUSIONS: The number of melanoma cases in the Czech Republic is increasing faster than any other cancer. Despite improved survival rates, the death rate from CM continues to climb as a result of exponential increases in incidence. Thus primary and secondary prevention campaigns are essential for future reductions in CM incidence and mortality in the Czech Republic.
Keywords: dospělí; Female; Adult; ženské pohlaví; lidé; staging nádorů; Aged, 80 and over; míra přežití; nádory kůže; Risk Factors; Incidence; Male; melanom; incidence; Aged; Czech Republic; Skin Neoplasms; rizikové faktory; Survival Rate; Česká republika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Neoplasm Staging; Melanoma; Humans